2008
DOI: 10.1002/cne.21654
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin receptor‐like receptor (CLR), receptor activity‐modifying protein 1 (RAMP1), and calcitonin gene‐related peptide (CGRP) immunoreactivity in the rat trigeminovascular system: Differences between peripheral and central CGRP receptor distribution

Abstract: CGRP meets its receptor in the rat dura mater. The CGRP receptor protein CLR (green) is expressed in smooth muscle cells (blue, SMA) in the media of meningeal arteries (left) but not in veins (right upper half). CLR is also found in trigeminal nerve bundles and mononuclear cells adjacent to the arteries. CGRP‐receptor components are however not co‐localized with axonal CGRP (red) in the dura, but expressed in Schwann cells (not visible at this magnification). J. Comp. Neurol. 507:1279–1301, 2008. © 2008 Wiley‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 0 publications
6
87
1
Order By: Relevance
“…We observed that neurons positive for CGRP were mostly negative for the receptor components CLR and RAMP1. Almost 50% of human trigeminal neurons expressed CGRP, which is in agreement with previous studies in man (Tajti et al, 1999) and rat (Ma et al, 2001, Lennerz et al, 2008. Expression of CLR and RAMP1 was seen in approximately 40% of the neurons.…”
Section: The Distribution Of Cgrp and The Receptor Componentssupporting
confidence: 91%
See 4 more Smart Citations
“…We observed that neurons positive for CGRP were mostly negative for the receptor components CLR and RAMP1. Almost 50% of human trigeminal neurons expressed CGRP, which is in agreement with previous studies in man (Tajti et al, 1999) and rat (Ma et al, 2001, Lennerz et al, 2008. Expression of CLR and RAMP1 was seen in approximately 40% of the neurons.…”
Section: The Distribution Of Cgrp and The Receptor Componentssupporting
confidence: 91%
“…Expression of CLR and RAMP1 was seen in approximately 40% of the neurons. In a study on rat trigeminal ganglion, it was reported that CLR was more frequently expressed than RAMP1 in the neurons (Lennerz et al, 2008). The dissimilarity between these results and ours could be due to several factors such as the use of different primary antibodies, cell-counting method or differences between human and rat trigeminal ganglia.…”
Section: The Distribution Of Cgrp and The Receptor Componentscontrasting
confidence: 80%
See 3 more Smart Citations